2020
DOI: 10.1021/acsaem.0c01661
|View full text |Cite
|
Sign up to set email alerts
|

Study of TiO2-Coated α-Fe2O3 Composites and the Oxygen-Defects Effect on the Application as the Anode Materials of High-Performance Li-Ion Batteries

Abstract: TiO 2 -coated Fe 2 O 3 composites exhibiting high electrochemical stability with oxygen defects were synthesized as the anode materials of Li-ion batteries using an easy sol−gel method. The industrial submicron-sized Fe 2 O 3 with no special shape and commercial tetrabutyl titanate were adopted as raw materials. The phase structures, morphologies, and elements distribution on the surface were characterized by X-ray diffraction analysis, electron paramagnetic resonance, scanning electron microscopy, X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…It has been demonstrated that oxygen vacancies, not only facilitate faster charge transport kinetics, but are also beneficial to retain the integrity of the electrode structure, thus enhancing the electrochemical activity. 22 As shown in Fig. 4, the morphologies and microstructure of the Fe 2 O 3 spindles, Fe 2 O 3 @SiO 2 , Fe 2 O 3 @SiO 2 @PDA and YS-Fe 2 O 3 @NC composites, were examined by SEM and TEM.…”
Section: Pccp Papermentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that oxygen vacancies, not only facilitate faster charge transport kinetics, but are also beneficial to retain the integrity of the electrode structure, thus enhancing the electrochemical activity. 22 As shown in Fig. 4, the morphologies and microstructure of the Fe 2 O 3 spindles, Fe 2 O 3 @SiO 2 , Fe 2 O 3 @SiO 2 @PDA and YS-Fe 2 O 3 @NC composites, were examined by SEM and TEM.…”
Section: Pccp Papermentioning
confidence: 99%
“…19,20 Oxygen vacancies in transition metal oxides are significant owing to their role as electron donors. 21 For example, Ma et al 22 reported a yolk@shell structure of TiO 2 @Fe 2 O 3 with oxygen vacancies for LIBs. These oxygen vacancies in Fe 2 O 3 served as shallow donors, and effectively improved the electronic properties of Fe 2 O 3 nanostructures, leading to excellent rate capability and superior cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…On proof of this concept, herein, we report a twoin-one shell configuration of carbon and titanium dioxide for bimetal selenides to achieve fast and stable sodium storage within broadened voltage windows. Titanium dioxide quantum dots with high ionic conductivity and the "zero-strain" characteristic are expected to allow fast pass-through and uptake of Na + without degrading the structure, [32][33][34] while the conductive amorphous carbon could construct a fast electric path. 35 Therefore, the structurally engineered Ni-CoSe 2 anode, integrating the merits of titanium dioxide quantum dots/amorphous carbon hybridized shell (Ni-CoSe 2 @TQDs/AC), can not only effectively buffer the strain and maintain the structural integrity but also allow fast and reversible transport of electrons/ions, resulting in increased reaction kinetics and high rate of Na storage.…”
Section: Introductionmentioning
confidence: 99%
“…4a). 15 It was noticed that Fe 2+ also existed in the sample, which may be attributed to the considerable number of defect sites with low oxygen coordination bonds. Based on the different electronic states of N heteroatoms, the deconvoluted N 1s high-resolution spectrum contains peaks at 404.3 401.7, 400.9 and 398.7 eV representing four N species, which can be assigned as pyridinic oxide (16%), graphitic-N (21%), pyrrolic-N (25%) and pyridinic-N (38%), respectively (Fig.…”
mentioning
confidence: 95%
“…10 Recently, various strategies have been developed to improve the electrochemical performances of transition-metal oxides, such as structural amelioration (e.g. monophasic and polyphasic synthesis), 11 crystallinity modulation (single crystal, polycrystal or amorphism), 12,13 defect engineering (surface and crystal heteroatom doping), [14][15][16] composition modification (hybridization with carbon or metal, changing the element valence, or reducing the inserted Li content), [17][18][19] morphological control (zero-, one-, two-, and three-dimensional structures, nanostructuring, porosity, structural hierarchy, and surface and interface regulation) [20][21][22] and so forth. These strategies inspired us to rationally design and synthesize an anode material system with a unique structure and morphology to enhance the electrochemical performance.…”
mentioning
confidence: 99%